Ali Al Bazergan and its impact on the intellectual, political and administrative in Iraq 1887-1958 Historical Study (Journal of the College of Education for Women, 2019)
The historical person study as a personality to the AL- Bazargan, one of the importantstudies, is the shed light on the character had an effect of the political life in Iraq, an importanthistorical era involved many events, coincided with a national and historical by this personalat the events successive positions that stage of the history of Iraq, especially if we know,strongly his loyalty to the homeland and the earth, and intense hatred for any occupation orcolonization desecrate the land...This was evident during his participation and his supervisor in 1920 liberal revolutionagainst the British occupation, and urged the need for adherence to the principles ofindependence, and the emphasis on the national cause.Patriotism and principles were evident, through his strong interest and directsupervision to open new schools at the time, in order to inform and educate a new generationof sons, and the consolidation of national values in them, and of patriotism and rejection ofcolonialism, and therefore the country's dependence on his children and not on the intrudersfrom the colonial powers.Intellectual productions also reflected the qualities and national goals, stressing thecultural marks on the Islamic religion and its impact on social urbanization and urbanizationof all Arab societies menu.We could say, that Ali AL- Bazerkan have left a mark and clear, and a large footprintin Iraq's modern history, to tender his successor from wealthy, and national positions andauthentic indicated the originality manners and sense of national higher.